Analysis of water, sanitation, and hygiene facilities using the WASH-FIT approach and its relation to patient satisfaction and maternal mortality at hospitals in Indonesia - Rina Purwandari; D. Daniel; Firdaus Hafidz (Frontiers Media S.A., 2024)
IntroductionThe provision of Water, Sanitation, and Hygiene (WASH) is critical to reducing infection and enhancing the quality of health care services. The study aims to assess WASH facilities in Indonesian hospitals using the Water, Sanitation, and Hygiene Facility Improvement Tool (WASH-FIT) approach and examine their association with customer satisfaction and maternal mortality owing to infection.MethodsWe utilized the national scale Health Facilities Research dataset in Indonesian hospitals in 2019. WASH status is determined using WASH-FIT indicators, i.e., water, sanitation, waste management, hand hygiene, environmental cleaning, and management services, and then divided into three levels: poor, adequate, and good categories.ResultsThe majority of hospitals in Indonesia had a good category, i.e., the range of hospitals with a good category was 79-97% nationally, in 6 aspects: water, sanitation, hand hygiene, environmental cleaning, and management services, except for waste management services (13%). Good WASH service facilities are more frequently found in government hospitals than in private and specialized hospitals, while lower-level hospitals tend to have poor levels of all WASH-FIT indicators. There are significant relationships between adequate sanitation services (β = 0.724), adequate and good categories of hand hygiene services (β = 0.712 and 0.866, respectively), environmental cleaning (β = −0.501 and -0.503, respectively), and management (β = −0.645 and 0.446, respectively), with the proportion of maternal mortality owing to infection. Furthermore, there was no relationship between WASH-FIT indicators and patient satisfaction, except for good hand hygiene services (β = 0.453).DiscussionDespite good conditions in almost all WASH-FIT indicators, the improvement of waste management is urgently needed to improve the WASH services in hospitals in Indonesia, as also found in other developing countries.